Venom of the Coral Snake Micrurus clarki: Proteomic Profile, Toxicity, Immunological Cross-Neutralization, and Characterization of a Three-Finger Toxin - Bruno Lomonte; Mahmood Sasa; Paola Rey-Suárez; Wendy Bryan; José María Gutiérrez (Toxins, 2016)
Micrurus clarki is an uncommon coral snake distributed from the Southeastern Pacific of Costa Rica to Western Colombia, for which no information on its venom could be found in the literature. Using a ‘venomics’ approach, proteins of at least nine families were identified, with a moderate predominance of three-finger toxins (3FTx; 48.2%) over phospholipase A2 (PLA2; 36.5%). Comparison of this venom profile with those of other Micrurus species suggests that it may represent a more balanced, ‘intermediate’ type within the dichotomy between 3FTx- and PLA2-predominant venoms. M. clarki venom was strongly cross-recognized and, accordingly, efficiently neutralized by an equine therapeutic antivenom against M. nigrocinctus, revealing their high antigenic similarity. Lethal activity for mice could be reproduced by a PLA2 venom fraction, but, unexpectedly, not by fractions corresponding to 3FTxs. The most abundant venom component, hereby named clarkitoxin-I, was identified as a short-chain (type I) 3FTx, devoid of lethal effect in mice, whose target remains to be defined. Its amino acid sequence of 66 residues shows high similarity with predicted sequences of venom gland transcripts described for M. fulvius, M. browni, and M. diastema.